Personal values and caring behaviours in student nurses at a university in Huanuco, Peru - Martel y Chang, Silvia Alicia (2019)
Objective. To determine the relationship between personal values and humanized caring behaviour. Methods. An observational, transversal and prospective correlational study carried out in 2019 in student nurses of hermilio valdizan university in huánuco-perú. population of 132 students. the personal values scale and the nursing care behaviour scale were used. pearson s correlation r test was used to test hypotheses. Results. The overall level of humanized caring behaviour perceived by students was optimal 86.4 % and personal values were high 87.1 %. on the other hand, a significant relationship was found between personal values and humanized caring behaviour, with p < 0,000. likewise, a significant relationship was found between humanized caring behaviour and the personal value dimensions of benevolence, hedonism, achievement, power, security, conformity and tradition all of them with p < 0,000. Conclusions. A relationship between personal values and humanized caring behaviour was found in student nurses of hermilio valdizan national university from Huanuco.